Columbian Exposition Waltz - Andrew Herman::::::::: (Carl Fisher)
Piano score, 10 p. At head of title: To Thomas W. Palmer, President of the Worlds Columbian Exposition. On cover is a lithograph in color of an allegorical figure sketching Machinery Hall, drawn